The Foundations of Epistemic Decision Theory. Issue 509 (4th April 2017) - Konek, Jason; Levinstein, Benjamin A
Abstract: According to accuracy-first epistemology, accuracy is the fundamental epistemic good. Epistemic norms–Probabilism, Conditionalization, the Principal Principle, and so on–have their binding force in virtue of helping to secure this good. To make this idea precise, accuracy-firsters invoke Epistemic Decision Theory (epdt ) to determine which epistemic policies are the best means toward the end of accuracy. Hilary Greaves and others have recently challenged the tenability of this programme. Their arguments purport to show that epdt encourages obviously epistemically irrational behaviour. We develop firmer conceptual foundations for epdt . First, we detail a theory of praxic and epistemic good. Then we show that, in light of their very different good-making features, epdt will evaluate epistemic states and epistemic acts according to different criteria. So, in general, rational preference over states and acts won't agree. Finally, we argue that based on direction-of-fit considerations, it is preferences over the former that matter for normative epistemology, and that epdt, properly spelt out, arrives at the correct verdicts in a range of putative problem cases.